Pengaruh Vaksinasi Pada Anjing Terhadap Tingkat Penularan Rabies Menggunakan Pemodelan Dinamik - Ludji, Dian Grace; Bobu, Fetronela Rambu (Pendidikan Matematika Universitas PGRI Yogyakarta, 2025)
Rabies is a disease that attacks the central nervous system (brain) caused by the rabies virus. Rabies is the most frightening infectious disease in the province of East Nusa Tenggara (NTT) where two people in TTU district were reported to have died from the Rabies virus due to being exposed to GHPR. This research was conducted to see the effect of vaccination on dogs on the rate of rabies transmission. The method used is to first create a mathematical model of rabies transmission by adding vaccination variables, then conducting numerical analysis and simulation. The model formed is . This model is formed to see the effect of vaccination in animals on the transmission of rabies in humans. This model has two equilibrium points, namely a disease-free equilibrium point with the results of the analysis of its stability conditions being locally asymptotically stable when and a disease-endemic equilibrium point with its stability conditions being unstable when . This means that rabies will disappear within a certain period of time. Numeric simulation was performed to support the analysis results using MAPLE software. The simulation results show that in more than 120 days rabies will disappear. Vaccination has a significant impact on the transmission of rabies, that is, the greater the rate of vaccination, the faster it will stop the transmission of rabies. Keywords: Dynamic Model, Rabies Transmission, Rabies Vaccine